Recurrent Vulvovaginal Candidiasis - Cyntya Sari Sovianti; Mutia Devi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Vulvovaginal candidiasis is a common fungal infection caused by Candida Sp, especially Candida albicans. Recurrent vulvovaginal candidiasis was defined as the occurrence of four or more episodes of vulvovaginal candidiasis ​​in 12 months period. As many as 9% of women from various populations have recurrent vulvovaginal candidiasis. Vulvovaginal candidiasis affects the quality of life, mental health, and sexual activity. There are many predisposing factors that caused recurrent vulvovaginal candidiasis, such as genetics, host, habit, idiopathic and non-albican candida microbes. Management of recurrent vulvovaginal candidiasis includes elimination of predisposing factors; mycological culture diagnosis and identification of specific Candida species; followed by microbiological examination to confirm the sensitivity of the azole group to Candida sp. Further, oral, or topical therapy should be continued until the patient is asymptomatic and culture-negative. Patients should receive induction therapy followed by maintenance suppressive therapy for six months.